PERANAN KUNYIT ASAM SEBAGAI ANTIOKSIDAN PADA FOTOOKSIDASI MINYAK KEDELAI - Rumiarsa, Komang; Suhendra, Lutfi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 3 (2018): September, 2018)
Turmeric tamarind is known for its strong antioxidant synergism which has the potential as a singlet oxygen catcher due to the presence of bioactive compounds that are easily oxidized by singlet oxygen. The aims of this study is to determine the role of turmeric- tamarind extract ( Curcuma domestica  Val.- Tamarindus indica  L.) as an antioxidant for erythrosine photosensitizer in soybean oil. Turmeric and tamarind are extracted using ethanol solution. The comparison of the turmeric tamarind extract used is 3: 2 with the total extract mixture concentration is 300 ppm. Photo-oxidation is determined by placing the soybean oil under fluorescent light 500, 1000, 1500, 2000, 2500, 3000 lux for 4 hours at room temperature. The ferithiocyanate method is used to measure peroxide figures for every hour. Descriptive one factor was used in analyzing the collected data. The results showed that the light intensity affected the damage of soybean oil containing 25 ppm erythrosine and turmeric-tamarind extract. Rapid damage of soybean oil that exposed to bright light is 18,5  time in comparation with dark conditions. Turmeric-tamarind extract has no activity as quenching singlet oxygen, but is effective as scaveging free radical. Keywords :  Soybean oil,  Curcuma domestica , Val.- Tamarindus indica  L., singlet oksigen quenching, scavenging free radical